Phase Transitions in Oil Disperse Systems and their Influence on the Thermochemical Process of Oil Dehydration - Lyudmila Semikhina; Irina Kovaleva; Dmitry Semekhin (Qubahan Academic Journal)
It is established that within the temperature range of oil dehydration in the fields, a phase transition occurs in oils, accompanied by a multifold change in the particle size of their dispersed phase. The study examines the method of assessing the temperature T* at which this process occurs based on the temperature dependence of oil viscosity. It is found that with T>T*, there are two effects taking place in oils that change the stability of oil-water emulsions in two opposite directions. Specifically, the reduction of oil viscosity facilitates a decrease in emulsion stability. In turn, increased emulsion stability is promoted by a rise in the content of natural emulsifiers in the oil disperse medium at T>T* due to a phase transition with a dramatic change in the particle size of the disperse phase. Therefore, the maximum speed and degree of oil dehydration is achieved at T*, which is confirmed experimentally. As a result, the need for a critical analysis of the oil treatment temperature regime used in the fields considering phase transitions within the particles of its dispersed phase is shown.